Теперішній тривалий час у контексті когнітивної граматики - Шпак, Ольга Андріївна; Shpak, O. А. (Східноєвропейський національний університет імені Лесі Українки, 2013)
Зроблено спробу проаналізувати теперішній тривалий час у контексті когнітивної граматики як результат процесу інтегрування основи теперішнього часу і форми дієслова. Розглянуто два випадки вживання тепе¬рішнього тривалого часу: теперішній у розвитку в момент мовлення з імплікацією незавершеності дії і тепе¬рішній у момент мовлення, який указує на заплановане закінчення дії. The Present Progressive Tense is analyzed in the article as a result of the process of integration of the present tense grounding and the form of the verb, generating a new semantic structure, a new profile/base alignment. The crucial facet to the meaning of –ing-form is that it focuses on the inside of the process, profiling effective homogeneity of its internal series. Two prototypical meanings of thе Present Progressive Tense are categorized: present in progress at the moment of speaking with the implication that the accomplishment is not guaranteed and present at the moment of speaking indicating intended termination. The semantic contribution of the concept present and the meaning of predication elaborating the clausal head are defined. In the Present Progressive Tense the verb realizes the traditional progressive aspect and the present tense morpheme grounds a composite structure.
The Present Progressive Tense in the Context of Cognitive Grammar
Keywords: фрейм; frame; профіль; profile; база; base